Interrelationships of factors causing delays in the relocation of utilities: A cognitive mapping approach. Issue 3 (16th May 2016) - Vilventhan, Aneetha; Kalidindi, Satyanarayana N.
Abstract : Purpose: – Relocation of utilities is a major source of delay in Indian infrastructure projects. This delay is particularly critical in road and bridge construction projects. The purpose of this paper is to identify the various factors and also the interrelationships between the factors which influence the delays in the relocation of utilities. Design/methodology/approach: – Case studies were conducted on 11 road and bridge projects in India with varying levels of complexity and size. Factors causing relocation delays were identified using computer aided qualitative analysis methodology. Cognitive mapping technique was used to map the interrelationships between the factors and to identify the critical delay factors. Findings: – Factors affecting delays were identified across two groups, namely, technical and organizational factors. The study offers insights into the kinds of interactions of factors that can lead to delays in a project. The critical factors causing delays were identified as slow response from utility agencies, difficulty in identification of underground utilities, lack of information on underground utilities and conflict between agencies. Research limitations/implications: – The limitations of the study are that the interview respondents are not evenly distributed among the type of organizations which may have induced some bias in responses. The impact of the utility relocation delays on the overall project delay has to be detailed further. Practical implications: – The interrelationships between factors has the potential to help the officials of highway department, contractors, utility agencies and others understand how various interactions/linkages of factors contributes to delays in utility relocations. Recommendations are provided for the practical use and to reduce the impact of delays. Originality/value: – Utility relocation has received very little attention in the extant literature and this paper seeks to contribute to knowledge in this area by identifying the linkages between factors and the critical factors of utility relocation delays in India.